High performance olefin polymer based composites
By preparing antistatic flame-retardant composite filler and high-low temperature resistant composite coating, combined with polypropylene powder and cellulose, high-strength polypropylene-based battery shell material is prepared by injection molding, solving the strength and heat resistance of existing materials and the problem of insufficient flame retardant performance have achieved the performance improvement of the high-performance battery case.
Patent Information
- Application Number
- CN202411365138.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
AI Technical Summary
The strength, heat resistance and flame retardant properties of the existing polypropylene-based battery shell materials are insufficient, making it difficult to meet the high requirements of high-performance battery shells for strength, rigidity, heat resistance and safety.
By preparing antistatic flame retardant composite fillers, phase change microcapsules, high-temperature resistant nanopowders and high-low temperature resistant composite coatings, combined with polypropylene powders, cellulose and other fillers, high-strength polypropylene bases are prepared by injection molding process. Battery housing material.
It significantly improves the antistatic properties, flame retardant properties and high and low temperature resistance of polypropylene materials, improves the strength, heat resistance and safety of the materials, and meets the needs of high-performance battery shells.
Smart Images

Figure CN119463252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-performance olefin polymer-based composite material and a preparation method thereof. Background Art
[0002] As an indispensable energy storage and conversion device in modern technology, batteries are widely used in electric vehicles, energy storage systems, consumer electronics and other fields. Among them, the battery casing is a key component to protect the battery cell from the external environment, and its performance directly affects the overall safety and reliability of the battery. Polypropylene is one of the commonly used materials for manufacturing battery casings due to its good processing performance, cost-effectiveness and chemical stability. However, with the rapid development of battery technology, higher requirements are placed on the strength, heat resistance, flame retardancy and other properties of the battery casing.
[0003] At present, polypropylene-based battery shell materials and their manufacturing methods mainly have the following problems: the mechanical properties of ordinary polypropylene are limited, and it is difficult to meet the strength and rigidity requirements of high-performance battery shells, especially when used under extreme conditions; polypropylene has poor heat resistance and is prone to deformation when exposed to high temperature for a long time, affecting the stability and safety of the battery; the battery may overheat or short-circuit during use, and the flame retardant properties of polypropylene-based battery shell materials are insufficient, which increases safety risks.
[0004] Therefore, we proposed a high-strength polypropylene-based battery shell material and a method for manufacturing a battery shell. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a high-strength polypropylene-based battery shell material and a method for manufacturing a battery shell.
[0006] A method for manufacturing a high-strength polypropylene-based battery shell material comprises the following steps: S1: Preparation of antistatic and flame retardant composite fillers The calcined fly ash solution is mixed with the antimony-doped tin oxide solution to obtain a precipitate, the precipitate is calcined and ground to obtain an antistatic powder, the antistatic powder, water, magnesium chloride and sodium hydroxide are mixed and reacted, and then washed, filtered and dried to obtain an antistatic flame retardant composite filler; S2: Preparation of phase change microcapsules Phase change microcapsules are prepared by encapsulating n-eicosane in microcapsules; S3: Preparation of PDMA-SH homopolymer PDMA-DOPAT homopolymer was synthesized with DMA and DOPAT chain transfer agent as raw materials, and PDMA-SH homopolymer was prepared through PDMA-DOPAT homopolymer; S4: Preparation of high temperature resistant nanopowders After preparing the nano powder, KH-570 is used to modify it, and PDMA-SH homopolymer, modified nano powder and tetrahydrofuran are mixed and reacted to obtain a reaction solution, which is cooled, centrifuged, washed and dried to obtain a high temperature resistant nano powder; S5: Preparation of high and low temperature resistant composite coatings The high and low temperature resistant composite coating is prepared with modified cellulose, high temperature resistant nano powder, phase change microcapsule, silica aerogel, styrene acrylic emulsion and inorganic silica sol solution as raw materials; S6: Preparation of polypropylene-based battery shell materials A polypropylene-based battery shell material is prepared according to the raw materials of 100-120 parts by weight of polypropylene powder, 6-8 parts by weight of low-density polyethylene, 6-8 parts by weight of high-density polyethylene, 0.3-0.5 parts by weight of antioxidant, 20-30 parts by weight of anti-static and flame-retardant composite filler, 2-3 parts by weight of basalt fiber, 1-2 parts by weight of carbon fiber, 0.5-1 parts by weight of zinc stearate and 1-2 parts by weight of distilled water.
[0007] Furthermore, step S1 of preparing the antistatic flame retardant composite filler specifically comprises the following steps: S1.1: calcining fly ash at 700-750°C for 10-12h to obtain calcined fly ash, and mixing 10-20 parts by weight of the calcined fly ash with 150-200 parts by weight of deionized water to obtain a calcined fly ash solution; S1.2: Add antimony trichloride and tin tetrachloride pentahydrate into a 36-38% hydrochloric acid solution to dissolve them, then add deionized water to prepare an antimony-doped tin oxide solution with a tin tetrachloride concentration of 0.4-0.5 mol / L, and the molar ratio of antimony trichloride to tin tetrachloride pentahydrate is 1-2:8; S1.3: Place the calcined fly ash solution in a container and stir it in a water bath at 60-65°C, and at the same time, drop 1-2 parts by weight of antimony-doped tin oxide solution at a rate of 1-2 mL / min. After the dropwise addition, adjust the pH to 8-9 with sodium hydroxide solution, continue the reaction for 30-40 minutes, and cool and settle for 50-60 minutes to obtain a precipitate; S1.4: After repeatedly washing the precipitate with deionized water for 2-3 times, drying it in an oven at 100-120°C for 7-8h, placing the dried precipitate in a muffle furnace and calcining it at 650-700°C for 1-2h, cooling it to room temperature and grinding it to obtain an antistatic powder; S1.5: Add 10-20 parts by weight of antistatic powder to 50-70 parts by weight of deionized water, stir evenly, then add 1-2 parts by weight of 0.15-0.2mol / L magnesium chloride solution and 1-2 parts by weight of 0.3-0.4mol / L sodium hydroxide solution at a rate of 1.2-1.5mol / L. After the addition is completed, react at 60-65°C for 1-2h. After the reaction is completed, wash, filter and dry to obtain an antistatic flame retardant composite filler.
[0008] Furthermore, the preparation of the phase change microcapsules in step S2 specifically includes the following steps: S2.1: 2-3 parts by weight of n-eicosane, 0.8-1 parts by weight of CTAB and 25-30 parts by weight of formamide are mixed and heated in an oil bath at 60-65° C., and stirred at 800-900 r / min for 2-3 hours, and then 10-20 parts by weight of a sodium sulfate solution with a concentration of 0.15-0.2 g / mL are added, and the pH is adjusted to 9-10 with sodium hydroxide, and stirring is continued for 3-4 hours to obtain an emulsion mixture; S2.2: Add 2-3 parts by weight of barium chloride to 17-20 parts by weight of deionized water, dissolve by magnetic stirring, add sodium hydroxide to adjust the pH to 9-10, then add 3-4 parts by weight of EDTA•2Na, stir and mix for 10-20 minutes to obtain a precursor solution; S2.3: Add the precursor solution to the emulsion mixture at a rate of 1-2 mL / min, and continue stirring to react for 2-3 hours to obtain the reactants. Separate the reactants to obtain precipitates, wash, filter, and dry the precipitates to obtain phase change microcapsules.
[0009] Furthermore, the preparation of the PDMA-SH homopolymer in step S3 specifically comprises the following steps: S3.1: 10-12 parts by weight of DMA, 0.7-0.8 parts by weight of DOPAT chain transfer agent, 0.04-0.05 parts by weight of AIBN initiator, and 30-32 parts by weight of 1,4-dioxane are added to a single-necked flask, nitrogen is introduced, and then heated to 65-68°C for reaction for 18-20 hours. After the reaction is completed, the mixture is placed in an ice water bath for cooling, 20-22 times the amount of n-hexane is added, and a precipitate is obtained after stirring, and the precipitate is washed, filtered, and dried to obtain a PDMA-DOPAT homopolymer; S3.2: Add 5-8 parts by weight of PDMA-DOPAT homopolymer, 1-2 parts by weight of n-hexylamine, 0.15-0.2 parts by weight of tributyl phosphine and 28-30 parts by weight of tetrahydrofuran into a single-necked flask, protect with nitrogen, heat to 40-45°C and react for 10-12 hours. After the reaction, cool in an ice water bath, add 20-22 times the amount of n-hexane, stir to obtain a precipitate, wash, filter and dry to obtain a PDMA-SH homopolymer.
[0010] Furthermore, step S4 of preparing the high temperature resistant nano powder specifically comprises the following steps: S4.1: Disperse 13-15 parts by weight of vanadium pentoxide powder into 400-500 parts by weight of deionized water and heat to 60-65°C, then add 5-6 parts by weight of hydrazine hydrate, and then put into a high-pressure reactor, react at 260-270°C for 24-25h, collect the reaction solution, centrifuge it, wash it with anhydrous ethanol, and dry it to obtain nano powder; S4.2: Add 1-2 parts by weight of the nanopowder to 100-120 parts by weight of anhydrous ethanol, and ultrasonically disperse for 20-30 minutes, then add ammonia water to adjust the pH to 9-10, add 0.05-0.1 parts by weight of KH-570, stir and mix, and react at 60-65°C for 6-8 hours. After the reaction is completed, centrifuge, wash and dry to obtain modified nanopowder; S4.3: 0.1-0.2 parts by weight of PDMA-SH homopolymer, 0.5-1 parts by weight of modified nanopowder and 18-20 parts by weight of tetrahydrofuran are placed in a single-necked flask and mixed, and ultrasonically dispersed for 30-40 minutes, and then 0.02-0.03 parts by weight of AIBN initiator are added. After mixing, nitrogen protection is applied, magnetic stirring is applied, and the mixture is heated to 60-65° C. for reaction for 24-25 hours to obtain a reaction solution; S4.4: Cool the reaction solution with an ice-water bath, centrifuge it with a centrifuge to obtain a precipitate, wash the precipitate with THF for 2-3 times, and dry the washed precipitate in a vacuum drying oven for 10-12 hours to obtain a high temperature resistant nano powder.
[0011] Furthermore, step S5 of preparing the high and low temperature resistant composite coating specifically comprises the following steps: S5.1: 20-30 parts by weight of silane coupling agent KH570, 70-80 parts by weight of anhydrous ethanol and 8-10 parts by weight of distilled water are mixed, and the pH is adjusted to 4-5 to obtain a coupling agent solution, 0.1-0.2 parts by weight of the coupling agent solution is added to 100-120 parts by weight of a cellulose-ethanol dilution solution having a concentration of 10-20%, and stirred at a speed of 1500-2000 r / min for 20-30 min, the suspension is taken out and vacuum filtered for 1-2 h, dried at 60-65° C. for 2-3 h, and left at room temperature for 12-14 h to obtain modified cellulose; S5.2: adding 2-3 parts by weight of modified cellulose to 100-120 parts by weight of deionized water, stirring and mixing to obtain a mixed solution, then adding 0.4-0.6 parts by weight of a dispersant, 0.6-1 parts by weight of a film-forming aid and 0.6-1 parts by weight of a defoaming agent, stirring at 1000-1200 r / min for 5-10 minutes to obtain a mixed emulsion; S5.3: Add 20-30 parts by weight of high temperature resistant nano powder, 15-20 parts by weight of phase change microcapsules and 2-5 parts by weight of silica aerogel to the mixed liquid, stir at 1500-2000 r / min for 30-40 min, then add 8-10 parts by weight of styrene acrylic emulsion, 25-30 parts by weight of inorganic silica sol solution and 0.1-0.3 parts by weight of thickener, stir at 1000-1200 r / min for 10-20 min to obtain a high and low temperature resistant composite coating.
[0012] Furthermore, step S6 of preparing a polypropylene-based battery casing material specifically comprises the following steps: S6.1: Prepare raw materials: 100-120 parts by weight of polypropylene powder, 6-8 parts by weight of low-density polyethylene, 6-8 parts by weight of high-density polyethylene, 0.3-0.5 parts by weight of antioxidant, 20-30 parts by weight of antistatic flame-retardant composite filler, 2-3 parts by weight of basalt fiber, 1-2 parts by weight of carbon fiber, 0.5-1 parts by weight of zinc stearate and 1-2 parts by weight of distilled water; S6.2: The above raw materials are placed in a high-speed mixer and mixed for 15-20 minutes to obtain a mixture, and the mixture is blended, extruded and granulated in a twin-screw extruder to obtain a blended polypropylene-based material, i.e., a polypropylene-based battery shell material.
[0013] Furthermore, in step S5, the film-forming aid includes at least one of dipropylene glycol butyl ether, alcohol ester dodeca, dipropylene glycol methyl ether, and propylene glycol butyl ether; the dispersant includes one of a block copolymer polyurethane or a long-chain linear acrylate; the thickener is a non-ionic hydrophobically modified polyurethane block copolymer; and the defoamer includes a non-ionic defoamer, a molecular-level defoamer, a mineral oil defoamer, or a silicone defoamer.
[0014] Furthermore, in step S6.1, the antioxidant is a mixture of antioxidant 1010 and DLTP in a weight ratio of 3-4:7.
[0015] A high-strength polypropylene-based battery shell, characterized in that the preparation of the polypropylene-based battery shell specifically includes the following steps: a: using a polypropylene-based battery shell material to prepare a polypropylene-based battery shell crude product by an injection molding process; b: coating the high and low temperature resistant composite coating on the crude polypropylene-based battery shell, and curing it under natural conditions to obtain a polypropylene-based battery shell; The propylene-based battery shell material and the high and low temperature resistant composite coating are prepared by any one of the methods for manufacturing the polypropylene-based battery shell material.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention can significantly improve the antistatic performance of polypropylene materials by adding antistatic flame retardant composite fillers to polypropylene. The antistatic flame retardant composite fillers can form a conductive network in the polypropylene material, thereby effectively reducing surface resistance, reducing static electricity accumulation, and preventing safety hazards caused by static electricity; the antistatic flame retardant composite fillers can improve the flame retardant performance of polypropylene, and nano-antimony doped tin oxide and other components can release flame retardant gas at high temperature to form a protective layer to prevent the spread of flames and reduce the combustion rate, thereby improving the safety of the material; the calcined fly ash can be distributed in the polypropylene matrix as a reinforcing phase, thereby improving the strength of the composite material and the friction effect of the interface, the interface strength is increased by 48.1%, the tensile strength reaches 450MPa, and the Young's modulus reaches 25Gpa, and each component in the antistatic flame retardant composite filler has high thermal stability, which can enhance the thermal stability of polypropylene, delay its degradation at high temperature, and improve the performance and life of the material in a high temperature environment.
[0017] 2. The present invention prepares antistatic powder by loading nano-antimony doped tin oxide on calcined fly ash to improve the dispersibility of nano-antimony doped tin oxide and reduce the volume resistivity of fly ash, and coats magnesium hydroxide on the surface of the antistatic powder to reduce the surface energy of magnesium hydroxide and enhance the flame retardant properties of the antistatic powder. Fly ash, magnesium hydroxide, and antimony doped tin oxide have a synergistic flame retardant effect. The prepared antistatic flame retardant composite filler has good antistatic flame retardant effect, so that the flame retardant grade (UL94) of the prepared battery shell is 1.5mm, V0 level, and can be used in power battery boxes of BYD / Ideal, etc.
[0018] 3. The present invention prepares a high and low temperature resistant composite coating, and coats it on the surface of a polypropylene-based battery shell, which can improve the high and low temperature resistance of the polypropylene-based battery shell, and realize the optimal working environment of the battery under high and low temperature extremes. The high temperature resistant nanopowder in the high and low temperature resistant composite coating can improve the high temperature resistance of the high and low temperature resistant composite coating. The added phase change microcapsules have effective thermal regulation ability and good chemical stability, and can store heat in a high temperature environment and release it in a low temperature environment, thereby regulating the temperature of the battery working environment. At the same time, the added silica aerogel also has a good thermal insulation effect. Therefore, through the synergistic effect of each component, the high and low temperature resistant composite coating has good thermal insulation and high and low temperature resistance, thereby improving the thermal insulation and high and low temperature resistance of the polypropylene-based battery shell.
[0019] 4. The present invention solves the problem of uneven dispersion of high-temperature resistant nanopowders in high- and low-temperature resistant composite coatings by constructing a core-shell structure with inorganic nanopowders and organic block polymers. The nanopowders are added to prepare high- and low-temperature resistant composite coatings. The nanopowders can fill tiny pores and defects in the coatings, enhance the bonding force between the coatings and the substrate material, and thus improve the adhesion of the coatings. The modified nanopowders and PDMA-SH homopolymers form stable chemical bonds through free radical polymerization. This structure can remain stable at high temperatures, so that the battery box remains unsoftened at 120°C for a long time, thereby improving the heat resistance of the composite material. The nanopowders are tightly combined with the PDMA-SH homopolymers through surface modification and covalent bonding to form a composite material. This composite material has high strength and, as a reinforcing phase, improves the strength of the high- and low-temperature resistant composite coatings, thereby further improving the strength of the polypropylene-based battery shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0021] Figure 1 This is a flow chart of a method for manufacturing a high-strength polypropylene-based battery shell material used in an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following is a detailed description of a method for manufacturing a high-strength polypropylene-based battery shell material provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods for some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0023] In the following Example 1, the reaction formula of the synthesis method of PDMA-SH homopolymer is as follows: Example
[0024] A method for manufacturing a high-strength polypropylene-based battery shell material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antistatic and flame retardant composite fillers S1.1: calcining fly ash at 700°C for 10 hours to obtain calcined fly ash, and mixing 10 parts by weight of calcined fly ash with 150 parts by weight of deionized water to obtain a calcined fly ash solution; S1.2: Add antimony trichloride and tin tetrachloride pentahydrate into a 36% hydrochloric acid solution to dissolve them, then add deionized water to prepare an antimony-doped tin oxide solution with a tin tetrachloride concentration of 0.4 mol / L, and the molar ratio of antimony trichloride to tin tetrachloride pentahydrate is 1:8; S1.3: The calcined fly ash solution was placed in a container and stirred in a water bath at 60°C, and 1 part by weight of antimony-doped tin oxide solution was added dropwise at a rate of 1 mL / min. After the addition was completed, the pH was adjusted to 8 with a sodium hydroxide solution. After the reaction was continued for 30 minutes, the solution was cooled and settled for 50 minutes to obtain a precipitate. S1.4: After washing the precipitate with deionized water for two times, the precipitate was dried in an oven at 100°C for 7 h, and the dried precipitate was placed in a muffle furnace and calcined at 650°C for 1 h. After cooling to room temperature, the precipitate was ground to obtain an antistatic powder; S1.5: Add 10 parts by weight of antistatic powder to 50 parts by weight of deionized water, stir evenly, then add 1 part by weight of 0.15 mol / L magnesium chloride solution and 1 part by weight of 0.3 mol / L sodium hydroxide solution at a rate of 1.2 mol / L, react at 60°C for 1 hour after the addition, wash, filter and dry after the reaction to obtain an antistatic flame retardant composite filler; S2: Preparation of phase change microcapsules S2.1: 2 parts by weight of n-eicosane, 0.8 parts by weight of CTAB and 25 parts by weight of formamide were mixed and heated in an oil bath at 60°C and stirred at 800 r / min for 2 h, and then 10 parts by weight of a 0.15 g / mL sodium sulfate solution was added, the pH was adjusted to 9 with sodium hydroxide, and the mixture was stirred for 3 h to obtain an emulsion mixture; S2.2: 2 parts by weight of barium chloride are added to 17 parts by weight of deionized water, and after dissolving by magnetic stirring, sodium hydroxide is added to adjust the pH to 9, and then 3 parts by weight of EDTA•2Na are added, and the mixture is stirred for 10 minutes to obtain a precursor solution; S2.3: adding the precursor solution to the emulsion mixture at a rate of 1 mL / min, stirring the mixture continuously for 2 h to obtain a reactant, separating the reactant to obtain a precipitate, washing, filtering and drying the precipitate to obtain phase change microcapsules; S3: Preparation of PDMA-SH homopolymer S3.1: 10 parts by weight of DMA, 0.7 parts by weight of DOPAT chain transfer agent, 0.04 parts by weight of AIBN initiator, and 30 parts by weight of 1,4-dioxane were added to a single-necked flask, nitrogen was introduced, and then heated to 65°C for reaction for 18 hours. After the reaction was completed, the mixture was placed in an ice-water bath for cooling, 20 times the amount of n-hexane was added, and the precipitate was obtained after stirring, which was washed, filtered, and dried to obtain a PDMA-DOPAT homopolymer; S3.2: 5 parts by weight of PDMA-DOPAT homopolymer, 1 part by weight of n-hexylamine, 0.15 parts by weight of tributyl phosphine, and 28 parts by weight of tetrahydrofuran were added to a single-necked flask, and heated to 40°C for 10 hours under nitrogen protection. After the reaction, the mixture was cooled in an ice-water bath, and 20 times the amount of n-hexane was added. The precipitate was obtained after stirring, and washed, filtered, and dried to obtain a PDMA-SH homopolymer; S4: Preparation of high temperature resistant nanopowders S4.1: 13 parts by weight of vanadium pentoxide powder is dispersed in 400 parts by weight of deionized water and heated to 60°C, and then 5 parts by weight of hydrazine hydrate is added, and then placed in a high-pressure reactor, reacted at 260°C for 24 hours, the reaction liquid is collected and centrifuged, washed with anhydrous ethanol, and dried to obtain nano powder; S4.2: 1 part by weight of the nanopowder is added to 100 parts by weight of anhydrous ethanol, and ultrasonically dispersed for 20 minutes, and then ammonia water is added to adjust the pH to 9, and 0.05 parts by weight of KH-570 is added, and the mixture is stirred and reacted at 60°C for 6 hours. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain a modified nanopowder; S4.3: 0.1 parts by weight of PDMA-SH homopolymer, 0.5 parts by weight of modified nanopowder and 18 parts by weight of tetrahydrofuran were placed in a single-necked flask and mixed, and ultrasonically dispersed for 30 minutes. Then, 0.02 parts by weight of AIBN initiator were added, and after mixing, nitrogen protection was applied, and the mixture was heated to 60° C. under magnetic stirring and reacted for 24 hours to obtain a reaction solution; S4.4: Cool the reaction solution with an ice-water bath, centrifuge with a centrifuge to obtain a precipitate, wash the precipitate with THF twice, and dry the washed precipitate in a vacuum drying oven for 10 hours to obtain a high temperature resistant nano powder; S5: Preparation of high and low temperature resistant composite coatings S5.1: 20 parts by weight of silane coupling agent KH570, 70 parts by weight of anhydrous ethanol and 8 parts by weight of distilled water were mixed, and the pH was adjusted to 4 to obtain a coupling agent solution. 0.1 parts by weight of the coupling agent solution was added to 100 parts by weight of a 10% cellulose-ethanol dilution solution, and the mixture was stirred at a speed of 1500 r / min for 20 min. The suspension was taken out and vacuum filtered for 1 h, dried at 60°C for 2 h, and left at room temperature for 12 h to obtain modified cellulose. S5.2: 2 parts by weight of modified cellulose are added to 100 parts by weight of deionized water, and the mixture is stirred to obtain a mixed solution. Then, 0.4 parts by weight of long-chain linear acrylate, 0.6 parts by weight of dipropylene glycol butyl ether and 0.6 parts by weight of a nonionic defoamer are added, and the mixture is stirred at 1000 r / min for 5 minutes to obtain a mixed emulsion. S5.3: Add 20 parts by weight of high temperature resistant nano powder, 15 parts by weight of phase change microcapsules and 2 parts by weight of silica aerogel to the mixed solution, stir at 1500 r / min for 30 min, then add 8 parts by weight of styrene acrylic emulsion, 25 parts by weight of inorganic silica sol solution and 0.1 parts by weight of thickener, stir at 1000 r / min for 10 min to obtain a high and low temperature resistant composite coating; S6: Preparation of polypropylene-based battery shell materials S6.1: Prepare raw materials: 100 parts by weight of polypropylene powder, 6 parts by weight of low-density polyethylene, 6 parts by weight of high-density polyethylene, 0.3 parts by weight of antioxidant, 20 parts by weight of antistatic flame-retardant composite filler, 2 parts by weight of basalt fiber, 1 part by weight of carbon fiber, 0.5 parts by weight of zinc stearate and 1 part by weight of distilled water, wherein the antioxidant is a mixture of antioxidant 1010 and DLTP in a weight ratio of 3:7; S6.2: The above raw materials are placed in a high-speed mixer and mixed for 15 minutes to obtain a mixed material, and the mixed material is blended, extruded and granulated through a twin-screw extruder to obtain a blended polypropylene-based material, i.e., a polypropylene-based battery casing material; The preparation of the polypropylene-based battery shell specifically includes the following steps: a: using a polypropylene-based battery shell material to prepare a polypropylene-based battery shell crude product by an injection molding process; b: The high and low temperature resistant composite coating is coated on the crude polypropylene-based battery shell, and after curing under natural conditions, a polypropylene-based battery shell is obtained. Example
[0025] A method for manufacturing a high-strength polypropylene-based battery shell material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antistatic and flame retardant composite fillers S1.1: calcining fly ash at 750°C for 12 hours to obtain calcined fly ash, and mixing 10 parts by weight of calcined fly ash with 150 parts by weight of deionized water to obtain a calcined fly ash solution; S1.2: Add antimony trichloride and tin tetrachloride pentahydrate into a 36% hydrochloric acid solution to dissolve them, then add deionized water to prepare an antimony-doped tin oxide solution with a tin tetrachloride concentration of 0.4 mol / L, and the molar ratio of antimony trichloride to tin tetrachloride pentahydrate is 1:8; S1.3: The calcined fly ash solution was placed in a container and stirred in a water bath at 65°C, and 1 part by weight of antimony-doped tin oxide solution was added dropwise at a rate of 1 mL / min. After the addition was completed, the pH was adjusted to 8 with a sodium hydroxide solution. After the reaction was continued for 40 minutes, the solution was cooled and settled for 60 minutes to obtain a precipitate. S1.4: After the precipitate is washed repeatedly with deionized water for 3 times, it is dried in an oven at 120°C for 8 h, the dried precipitate is placed in a muffle furnace and calcined at 700°C for 2 h, and then ground after cooling to room temperature to obtain an antistatic powder; S1.5: Add 10 parts by weight of antistatic powder to 50 parts by weight of deionized water, stir evenly, then add 1 part by weight of 0.15 mol / L magnesium chloride solution and 1 part by weight of 0.3 mol / L sodium hydroxide solution at a rate of 1.2 mol / L, react at 65°C for 2h after the addition, wash, filter and dry after the reaction to obtain an antistatic flame retardant composite filler; S2: Preparation of phase change microcapsules S2.1: 2 parts by weight of n-eicosane, 0.8 parts by weight of CTAB and 25 parts by weight of formamide were mixed and heated in an oil bath at 65°C and stirred at 900 r / min for 3 h, then 10 parts by weight of a 0.15 g / mL sodium sulfate solution was added, the pH was adjusted to 9 with sodium hydroxide, and the mixture was stirred for 4 h to obtain an emulsion mixture; S2.2: 2 parts by weight of barium chloride are added to 17 parts by weight of deionized water, and after dissolving by magnetic stirring, sodium hydroxide is added to adjust the pH to 9, and then 3 parts by weight of EDTA•2Na are added, and the mixture is stirred for 20 minutes to obtain a precursor solution; S2.3: adding the precursor solution to the emulsion mixture at a rate of 1 mL / min, stirring the mixture continuously for 3 h to obtain a reactant, separating the reactant to obtain a precipitate, washing, filtering and drying the precipitate to obtain phase change microcapsules; S3: Preparation of PDMA-SH homopolymer S3.1: 10 parts by weight of DMA, 0.7 parts by weight of DOPAT chain transfer agent, 0.04 parts by weight of AIBN initiator, and 30 parts by weight of 1,4-dioxane were added to a single-necked flask, nitrogen was introduced, and then heated to 68°C for reaction for 20 hours. After the reaction was completed, the mixture was placed in an ice-water bath for cooling, 20 times the amount of n-hexane was added, and a precipitate was obtained after stirring. The precipitate was washed, filtered, and dried to obtain a PDMA-DOPAT homopolymer; S3.2: 5 parts by weight of PDMA-DOPAT homopolymer, 1 part by weight of n-hexylamine, 0.15 parts by weight of tributyl phosphine, and 28 parts by weight of tetrahydrofuran were added to a single-necked flask, and the mixture was heated to 45°C for 12 hours under nitrogen protection. After the reaction, the mixture was cooled in an ice-water bath, and 20 times the amount of n-hexane was added. The precipitate was obtained after stirring, and the precipitate was washed, filtered, and dried to obtain a PDMA-SH homopolymer. S4: Preparation of high temperature resistant nanopowders S4.1: 13 parts by weight of vanadium pentoxide powder is dispersed in 400 parts by weight of deionized water and heated to 65°C, and then 5 parts by weight of hydrazine hydrate is added, and then placed in a high-pressure reactor, reacted at 270°C for 25 hours, the reaction liquid is collected and centrifuged, washed with anhydrous ethanol, and dried to obtain nano powder; S4.2: Add 1 part by weight of the nanopowder to 100 parts by weight of anhydrous ethanol, and ultrasonically disperse for 30 minutes, then add ammonia water to adjust the pH to 9, add 0.05 parts by weight of KH-570, stir and mix, and react at 65°C for 8 hours. After the reaction is completed, centrifuge, wash and dry to obtain modified nanopowder; S4.3: 0.1 parts by weight of PDMA-SH homopolymer, 0.5 parts by weight of modified nanopowder and 18 parts by weight of tetrahydrofuran were placed in a single-necked flask and mixed, and ultrasonically dispersed for 40 minutes, and then 0.02 parts by weight of AIBN initiator were added. After mixing, nitrogen protection was applied, and the mixture was heated to 65° C. under magnetic stirring and reacted for 25 hours to obtain a reaction solution; S4.4: Cool the reaction solution with an ice-water bath, centrifuge with a centrifuge to obtain a precipitate, wash the precipitate with THF three times, and dry the washed precipitate in a vacuum drying oven for 12 hours to obtain a high temperature resistant nano powder; S5: Preparation of high and low temperature resistant composite coatings S5.1: 20 parts by weight of silane coupling agent KH570, 70 parts by weight of anhydrous ethanol and 8 parts by weight of distilled water were mixed, and the pH was adjusted to 4 to obtain a coupling agent solution. 0.1 parts by weight of the coupling agent solution was added to 100 parts by weight of a 10% cellulose-ethanol dilution solution, and the mixture was stirred at a speed of 2000 r / min for 30 min. The suspension was taken out and vacuum filtered for 2 h, dried at 65°C for 3 h, and left at room temperature for 14 h to obtain modified cellulose. S5.2: 2 parts by weight of modified cellulose are added to 100 parts by weight of deionized water, and the mixture is stirred to obtain a mixed solution. Then, 0.4 parts by weight of long-chain linear acrylate, 0.6 parts by weight of dipropylene glycol butyl ether and 0.6 parts by weight of a nonionic defoamer are added, and the mixture is stirred at 1200 r / min for 10 min to obtain a mixed emulsion. S5.3: Add 20 parts by weight of high temperature resistant nano powder, 15 parts by weight of phase change microcapsules and 2 parts by weight of silica aerogel to the mixed solution, stir at 2000 r / min for 40 min, then add 8 parts by weight of styrene acrylic emulsion, 25 parts by weight of inorganic silica sol solution and 0.1 parts by weight of thickener, stir at 1200 r / min for 20 min to obtain a high and low temperature resistant composite coating; S6: Preparation of polypropylene-based battery shell materials S6.1: Prepare raw materials: 100 parts by weight of polypropylene powder, 6 parts by weight of low-density polyethylene, 6 parts by weight of high-density polyethylene, 0.3 parts by weight of antioxidant, 20 parts by weight of antistatic flame-retardant composite filler, 2 parts by weight of basalt fiber, 1 part by weight of carbon fiber, 0.5 parts by weight of zinc stearate and 1 part by weight of distilled water, wherein the antioxidant is a mixture of antioxidant 1010 and DLTP in a weight ratio of 3:7; S6.2: The above raw materials are placed in a high-speed mixer and mixed for 20 minutes to obtain a mixed material, and the mixed material is blended, extruded and granulated through a twin-screw extruder to obtain a blended polypropylene-based material, i.e., a polypropylene-based battery casing material; The preparation of the polypropylene-based battery shell specifically includes the following steps: a: using a polypropylene-based battery shell material to prepare a polypropylene-based battery shell crude product by an injection molding process; b: The high and low temperature resistant composite coating is coated on the crude polypropylene-based battery shell, and after curing under natural conditions, a polypropylene-based battery shell is obtained. Example
[0026] A method for manufacturing a high-strength polypropylene-based battery shell material, such as Figure 1 As shown, the following steps are included: S1: Preparation of antistatic and flame retardant composite fillers S1.1: calcining fly ash at 700°C for 10 hours to obtain calcined fly ash, and mixing 10-20 parts by weight of calcined fly ash with 200 parts by weight of deionized water to obtain a calcined fly ash solution; S1.2: Add antimony trichloride and tin tetrachloride pentahydrate into a 38% hydrochloric acid solution to dissolve them, then add deionized water to prepare an antimony-doped tin oxide solution with a tin tetrachloride concentration of 0.5 mol / L, and the molar ratio of antimony trichloride to tin tetrachloride pentahydrate is 1:4; S1.3: The calcined fly ash solution was placed in a container and stirred in a water bath at 60°C, and 2 parts by weight of antimony-doped tin oxide solution was added dropwise at a rate of 2 mL / min. After the addition was completed, the pH was adjusted to 9 with a sodium hydroxide solution. After the reaction was continued for 30 minutes, the solution was cooled and settled for 50 minutes to obtain a precipitate. S1.4: After washing the precipitate with deionized water for two times, the precipitate was dried in an oven at 100°C for 7 h, and the dried precipitate was placed in a muffle furnace and calcined at 650°C for 1 h. After cooling to room temperature, the precipitate was ground to obtain an antistatic powder; S1.5: Add 20 parts by weight of antistatic powder to 70 parts by weight of deionized water, stir evenly, and then drop 2 parts by weight of 0.2 mol / L magnesium chloride solution and 2 parts by weight of 0.4 mol / L sodium hydroxide solution at a rate of 1.5 mol / L. After the dropwise addition, react at 60°C for 1 hour. After the reaction is completed, wash, filter and dry to obtain an antistatic flame retardant composite filler; S2: Preparation of phase change microcapsules S2.1: 3 parts by weight of n-eicosane, 1 part by weight of CTAB and 30 parts by weight of formamide were mixed and heated in an oil bath at 60°C and stirred at 800 r / min for 2 h, then 20 parts by weight of a 0.2 g / mL sodium sulfate solution was added, the pH was adjusted to 10 with sodium hydroxide, and the mixture was stirred for 3 h to obtain an emulsion mixture; S2.2: 3 parts by weight of barium chloride are added to 20 parts by weight of deionized water, and after dissolving by magnetic stirring, sodium hydroxide is added to adjust the pH to 10, and then 4 parts by weight of EDTA•2Na are added, and the mixture is stirred for 10 minutes to obtain a precursor solution; S2.3: adding the precursor solution to the emulsion mixture at a rate of 2 mL / min, stirring and reacting for 2 h to obtain a reactant, separating the reactant to obtain a precipitate, washing, filtering and drying the precipitate to obtain a phase change microcapsule; S3: Preparation of PDMA-SH homopolymer S3.1: 12 parts by weight of DMA, 0.8 parts by weight of DOPAT chain transfer agent, 0.05 parts by weight of AIBN initiator, and 32 parts by weight of 1,4-dioxane were added to a single-necked flask, nitrogen was introduced, and then heated to 65°C for reaction for 18 hours. After the reaction was completed, the mixture was placed in an ice-water bath for cooling, 22 times the amount of n-hexane was added, and a precipitate was obtained after stirring. The precipitate was washed, filtered, and dried to obtain a PDMA-DOPAT homopolymer; S3.2: 8 parts by weight of PDMA-DOPAT homopolymer, 2 parts by weight of n-hexylamine, 0.2 parts by weight of tributyl phosphine, and 30 parts by weight of tetrahydrofuran were added to a single-necked flask, and heated to 40°C for 10 hours under nitrogen protection. After the reaction, the mixture was cooled in an ice-water bath, and 22 times the amount of n-hexane was added. The precipitate was obtained after stirring, and washed, filtered, and dried to obtain a PDMA-SH homopolymer; S4: Preparation of high temperature resistant nanopowders S4.1: Disperse 15 parts by weight of vanadium pentoxide powder into 500 parts by weight of deionized water and heat to 60°C, then add 6 parts by weight of hydrazine hydrate, and then put into a high-pressure reactor, react at 260°C for 24 hours, collect the reaction solution, centrifuge it, wash it with anhydrous ethanol, and dry it to obtain nano powder; S4.2: 2 parts by weight of the nanopowder is added to 120 parts by weight of anhydrous ethanol, and ultrasonically dispersed for 20 minutes, and then ammonia water is added to adjust the pH to 10, and 0.1 parts by weight of KH-570 is added, and the mixture is stirred and reacted at 60°C for 6 hours. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain a modified nanopowder; S4.3: 0.2 parts by weight of PDMA-SH homopolymer, 1 part by weight of modified nanopowder and 20 parts by weight of tetrahydrofuran were placed in a single-necked flask and mixed, and ultrasonically dispersed for 30 minutes. Then, 0.03 parts by weight of AIBN initiator were added, and after mixing, nitrogen protection was applied, and the mixture was heated to 60° C. under magnetic stirring and reacted for 24 hours to obtain a reaction solution; S4.4: Cool the reaction solution with an ice-water bath, centrifuge with a centrifuge to obtain a precipitate, wash the precipitate with THF twice, and dry the washed precipitate in a vacuum drying oven for 10 hours to obtain a high temperature resistant nano powder; S5: Preparation of high and low temperature resistant composite coatings S5.1: 30 parts by weight of silane coupling agent KH570, 80 parts by weight of anhydrous ethanol and 10 parts by weight of distilled water were mixed, and the pH was adjusted to 5 to obtain a coupling agent solution. 0.2 parts by weight of the coupling agent solution was added to 120 parts by weight of a 20% cellulose-ethanol dilution solution, and the mixture was stirred at a speed of 1500 r / min for 20 min. The suspension was taken out and vacuum filtered for 1 h, dried at 60°C for 2 h, and left at room temperature for 12 h to obtain modified cellulose. S5.2: 3 parts by weight of modified cellulose are added to 120 parts by weight of deionized water, and the mixture is stirred to obtain a mixed solution. Then, 0.6 parts by weight of long-chain linear acrylate, 1 part by weight of dipropylene glycol butyl ether and 1 part by weight of a nonionic defoamer are added, and the mixture is stirred at 1000 r / min for 5 minutes to obtain a mixed emulsion. S5.3: Add 30 parts by weight of high temperature resistant nano powder, 20 parts by weight of phase change microcapsules and 5 parts by weight of silica aerogel to the mixed solution, stir at 1500 / min for 30 min, then add 10 parts by weight of styrene acrylic emulsion, 30 parts by weight of inorganic silica sol solution and 0.3 parts by weight of thickener, stir at 1000 r / min for 10 min to obtain a high and low temperature resistant composite coating; S6: Preparation of polypropylene-based battery shell materials S6.1: Prepare raw materials: 120 parts by weight of polypropylene powder, 8 parts by weight of low-density polyethylene, 8 parts by weight of high-density polyethylene, 0.5 parts by weight of antioxidant, 30 parts by weight of antistatic flame-retardant composite filler, 3 parts by weight of basalt fiber, 2 parts by weight of carbon fiber, 1 part by weight of zinc stearate and 2 parts by weight of distilled water, wherein the antioxidant is a mixture of antioxidant 1010 and DLTP in a weight ratio of 4:7; S6.2: The above raw materials are placed in a high-speed mixer and mixed for 15 minutes to obtain a mixed material, and the mixed material is blended, extruded and granulated through a twin-screw extruder to obtain a blended polypropylene-based material, i.e., a polypropylene-based battery casing material; The preparation of the polypropylene-based battery shell specifically includes the following steps: a: using a polypropylene-based battery shell material to prepare a polypropylene-based battery shell crude product by an injection molding process; b: The high and low temperature resistant composite coating is coated on the crude polypropylene-based battery shell, and after curing under natural conditions, a polypropylene-based battery shell is obtained.
[0027] Performance Test: Tensile strength and Young's modulus determination standard: GB / T1040.1-2018; Resistance measurement standard: GB / T37977.23-2019; Limiting oxygen index determination standard GB / T2406-2008; Flame retardant grade test: test method UL94, test condition 1.5mm.
[0028] Compared with Example 1, the difference of Comparative Example 1 is that the anti-static flame retardant composite filler in step S1 and step S6.1 is removed in Comparative Example 1, and the remaining steps remain unchanged to prepare the polypropylene-based battery shell, which is recorded as Comparative Example 1.
[0029] The performance of Examples 1-3 and Comparative Example 1 was measured, and the results are shown in Table 1.
[0030] Table 1. Performance measurement results of Examples 1-3 and Comparative Example 1
[0031] It can be seen from the data in Table 1 that the data of Comparative Example 1 are all lower than those of the embodiment, indicating that adding the antistatic flame retardant composite filler can improve the flame retardant properties of the polypropylene-based battery shell, effectively reduce the surface resistance, and improve the strength of the polypropylene-based battery shell.
[0032] Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes steps S2-S5 and step S6.3, and the other steps remain unchanged. The crude polypropylene-based battery shell is a polypropylene-based battery shell, which is recorded as Comparative Example 2.
[0033] The same battery was installed in the polypropylene-based battery casing of Examples 1-3 and Comparative Example 2, and a temperature control box was used to simulate a high temperature of 50°C and a low temperature of -20°C, respectively. The assembled polypropylene-based battery casings of Examples 1-3 and Comparative Example 2 were placed in the temperature control box. Under each temperature condition, the initial discharge capacity and internal resistance performance parameters of the battery were recorded. Constant current discharge was performed with the same current, and the discharge time was set to 2h. The discharge capacity and internal resistance of the battery under different temperature conditions were recorded, and the change rate was calculated. The measurement results are shown in Table 2.
[0034] Table 2. Changes in discharge capacity and internal resistance of Examples 1-3 and Comparative Example 2
[0035] According to the data in Table 2, it can be seen that the discharge capacity change rate and internal resistance change rate of Examples 1, 2, and 3 at two extreme temperatures of 50°C and -20°C are significantly lower than those of Comparative Example 2, which indicates that coating the high and low temperature resistant composite coating on the crude polypropylene-based battery shell can effectively improve the high and low temperature resistance of the polypropylene-based battery shell, reduce the change of discharge capacity and internal resistance, and thus help maintain the optimal working environment of the battery at extreme temperatures.
[0036] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes the high temperature resistant nano powder in steps S3-S4 and step S5.3, and the remaining steps remain unchanged polypropylene-based battery shell, which is recorded as Comparative Example 3.
[0037] The notched impact strength data of Example 1 was used to measure the notched impact strength of Comparative Examples 2-3. The measurement results are shown in Table 3.
[0038] Table 3. Notched impact strength test results of Example 1 and Comparative Examples 2-3
[0039] It can be seen from the data in Table 3 that the notched impact strength of Comparative Examples 2-3 is lower than that of Example 1, indicating that the high and low temperature resistant composite coating can improve the strength of the polypropylene-based battery shell, and the added high temperature resistant nanopowder as a reinforcing phase further improves the mechanical properties of the high and low temperature resistant composite coating, thereby effectively improving the strength of the polypropylene-based battery shell.
[0040] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for manufacturing a high-strength polypropylene-based battery shell material, characterized in that: The steps include: S1: Preparation of antistatic and flame retardant composite fillers The calcined fly ash solution is mixed with the antimony-doped tin oxide solution to obtain a precipitate, the precipitate is calcined and ground to obtain an antistatic powder, the antistatic powder, water, magnesium chloride and sodium hydroxide are mixed and reacted, and then washed, filtered and dried to obtain an antistatic flame retardant composite filler; S2: Preparation of phase change microcapsules Phase change microcapsules are prepared by encapsulating n-eicosane in microcapsules; S3: Preparation of PDMA-SH homopolymer PDMA-DOPAT homopolymer was synthesized with DMA and DOPAT chain transfer agent as raw materials, and PDMA-SH homopolymer was prepared through PDMA-DOPAT homopolymer; S4: Preparation of high temperature resistant nanopowders After preparing the nano powder, KH-570 is used to modify it, and PDMA-SH homopolymer, modified nano powder and tetrahydrofuran are mixed and reacted to obtain a reaction solution, which is cooled, centrifuged, washed and dried to obtain a high temperature resistant nano powder; S5: Preparation of high and low temperature resistant composite coatings The high and low temperature resistant composite coating is prepared with modified cellulose, high temperature resistant nano powder, phase change microcapsule, silica aerogel, styrene acrylic emulsion and inorganic silica sol solution as raw materials; S6: Preparation of polypropylene-based battery shell materials A polypropylene-based battery shell material is prepared according to the raw materials of 100-120 parts by weight of polypropylene powder, 6-8 parts by weight of low-density polyethylene, 6-8 parts by weight of high-density polyethylene, 0.3-0.5 parts by weight of antioxidant, 20-30 parts by weight of anti-static and flame-retardant composite filler, 2-3 parts by weight of basalt fiber, 1-2 parts by weight of carbon fiber, 0.5-1 parts by weight of zinc stearate and 1-2 parts by weight of distilled water.
2. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 1, characterized in that: Step S1: Preparation of antistatic flame retardant composite filler, specifically comprising the following steps: S1.1: calcining fly ash at 700-750°C for 10-12h to obtain calcined fly ash, and mixing 10-20 parts by weight of the calcined fly ash with 150-200 parts by weight of deionized water to obtain a calcined fly ash solution; S1.2: Add antimony trichloride and tin tetrachloride pentahydrate into a 36-38% hydrochloric acid solution to dissolve them, then add deionized water to prepare an antimony-doped tin oxide solution with a tin tetrachloride concentration of 0.4-0.5 mol / L, and the molar ratio of antimony trichloride to tin tetrachloride pentahydrate is 1-2:8; S1.3: Place the calcined fly ash solution in a container and stir it in a water bath at 60-65°C, and at the same time, drop 1-2 parts by weight of antimony-doped tin oxide solution at a rate of 1-2 mL / min. After the dropwise addition, adjust the pH to 8-9 with sodium hydroxide solution, continue the reaction for 30-40 minutes, and cool and settle for 50-60 minutes to obtain a precipitate; S1.4: After repeatedly washing the precipitate with deionized water for 2-3 times, drying it in an oven at 100-120°C for 7-8h, placing the dried precipitate in a muffle furnace and calcining it at 650-700°C for 1-2h, cooling it to room temperature and grinding it to obtain an antistatic powder; S1.5: Add 10-20 parts by weight of antistatic powder to 50-70 parts by weight of deionized water, stir evenly, then add 1-2 parts by weight of 0.15-0.2mol / L magnesium chloride solution and 1-2 parts by weight of 0.3-0.4mol / L sodium hydroxide solution at a rate of 1.2-1.5mol / L. After the addition is completed, react at 60-65°C for 1-2h. After the reaction is completed, wash, filter and dry to obtain an antistatic flame retardant composite filler.
3. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 2, characterized in that: Step S2: Preparation of phase change microcapsules, specifically comprising the following steps: S2.1: 2-3 parts by weight of n-eicosane, 0.8-1 parts by weight of CTAB and 25-30 parts by weight of formamide are mixed and heated in an oil bath at 60-65° C., and stirred at 800-900 r / min for 2-3 hours, and then 10-20 parts by weight of a sodium sulfate solution with a concentration of 0.15-0.2 g / mL are added, and the pH is adjusted to 9-10 with sodium hydroxide, and stirring is continued for 3-4 hours to obtain an emulsion mixture; S2.2: Add 2-3 parts by weight of barium chloride to 17-20 parts by weight of deionized water, dissolve by magnetic stirring, add sodium hydroxide to adjust the pH to 9-10, then add 3-4 parts by weight of EDTA•2Na, stir and mix for 10-20 minutes to obtain a precursor solution; S2.3: Add the precursor solution to the emulsion mixture at a rate of 1-2 mL / min, and continue stirring to react for 2-3 hours to obtain the reactants. Separate the reactants to obtain precipitates, wash, filter, and dry the precipitates to obtain phase change microcapsules.
4. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 3, characterized in that: Step S3: Preparation of PDMA-SH homopolymer, specifically comprising the following steps: S3.1: 10-12 parts by weight of DMA, 0.7-0.8 parts by weight of DOPAT chain transfer agent, 0.04-0.05 parts by weight of AIBN initiator, and 30-32 parts by weight of 1,4-dioxane are added to a single-necked flask, nitrogen is introduced, and then heated to 65-68°C for reaction for 18-20 hours. After the reaction is completed, the mixture is placed in an ice water bath for cooling, 20-22 times the amount of n-hexane is added, and a precipitate is obtained after stirring, and the precipitate is washed, filtered, and dried to obtain a PDMA-DOPAT homopolymer; S3.2: Add 5-8 parts by weight of PDMA-DOPAT homopolymer, 1-2 parts by weight of n-hexylamine, 0.15-0.2 parts by weight of tributyl phosphine and 28-30 parts by weight of tetrahydrofuran into a single-necked flask, protect with nitrogen, heat to 40-45°C and react for 10-12 hours. After the reaction, cool in an ice water bath, add 20-22 times the amount of n-hexane, stir to obtain a precipitate, wash, filter and dry to obtain a PDMA-SH homopolymer.
5. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 4, characterized in that: Step S4 is the preparation of high temperature resistant nano powder, which specifically comprises the following steps: S4.1: Disperse 13-15 parts by weight of vanadium pentoxide powder into 400-500 parts by weight of deionized water and heat to 60-65°C, then add 5-6 parts by weight of hydrazine hydrate, and then put into a high-pressure reactor, react at 260-270°C for 24-25h, collect the reaction solution, centrifuge it, wash it with anhydrous ethanol, and dry it to obtain nano powder; S4.2: Add 1-2 parts by weight of the nanopowder to 100-120 parts by weight of anhydrous ethanol, and ultrasonically disperse for 20-30 minutes, then add ammonia water to adjust the pH to 9-10, add 0.05-0.1 parts by weight of KH-570, stir and mix, and react at 60-65°C for 6-8 hours. After the reaction is completed, centrifuge, wash and dry to obtain modified nanopowder; S4.3: 0.1-0.2 parts by weight of PDMA-SH homopolymer, 0.5-1 parts by weight of modified nanopowder and 18-20 parts by weight of tetrahydrofuran are placed in a single-necked flask and mixed, and ultrasonically dispersed for 30-40 minutes, and then 0.02-0.03 parts by weight of AIBN initiator are added. After mixing, nitrogen protection is applied, magnetic stirring is applied, and the mixture is heated to 60-65° C. for reaction for 24-25 hours to obtain a reaction solution; S4.4: Cool the reaction solution with an ice-water bath, centrifuge it with a centrifuge to obtain a precipitate, wash the precipitate with THF for 2-3 times, and dry the washed precipitate in a vacuum drying oven for 10-12 hours to obtain a high temperature resistant nano powder.
6. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 5, characterized in that: Step S5 is the preparation of the high and low temperature resistant composite coating, which specifically comprises the following steps: S5.1: 20-30 parts by weight of silane coupling agent KH570, 70-80 parts by weight of anhydrous ethanol and 8-10 parts by weight of distilled water are mixed, and the pH is adjusted to 4-5 to obtain a coupling agent solution, 0.1-0.2 parts by weight of the coupling agent solution is added to 100-120 parts by weight of a cellulose-ethanol dilution solution having a concentration of 10-20%, and stirred at a speed of 1500-2000 r / min for 20-30 min, the suspension is taken out and vacuum filtered for 1-2 h, dried at 60-65° C. for 2-3 h, and left at room temperature for 12-14 h to obtain modified cellulose; S5.2: adding 2-3 parts by weight of modified cellulose to 100-120 parts by weight of deionized water, stirring and mixing to obtain a mixed solution, then adding 0.4-0.6 parts by weight of a dispersant, 0.6-1 parts by weight of a film-forming aid and 0.6-1 parts by weight of a defoaming agent, stirring at 1000-1200 r / min for 5-10 minutes to obtain a mixed emulsion; S5.3: Add 20-30 parts by weight of high temperature resistant nano powder, 15-20 parts by weight of phase change microcapsules and 2-5 parts by weight of silica aerogel to the mixed liquid, stir at 1500-2000 r / min for 30-40 min, then add 8-10 parts by weight of styrene acrylic emulsion, 25-30 parts by weight of inorganic silica sol solution and 0.1-0.3 parts by weight of thickener, stir at 1000-1200 r / min for 10-20 min to obtain a high and low temperature resistant composite coating.
7. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 6, characterized in that: Step S6: Preparation of polypropylene-based battery casing material, specifically comprising the following steps: S6.1: Prepare raw materials: 100-120 parts by weight of polypropylene powder, 6-8 parts by weight of low-density polyethylene, 6-8 parts by weight of high-density polyethylene, 0.3-0.5 parts by weight of antioxidant, 20-30 parts by weight of antistatic flame-retardant composite filler, 2-3 parts by weight of basalt fiber, 1-2 parts by weight of carbon fiber, 0.5-1 parts by weight of zinc stearate and 1-2 parts by weight of distilled water; S6.2: The above raw materials are placed in a high-speed mixer and mixed for 15-20 minutes to obtain a mixture, and the mixture is blended, extruded and granulated in a twin-screw extruder to obtain a blended polypropylene-based material, i.e., a polypropylene-based battery shell material.
8. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 6, characterized in that: In step S5, the film-forming aid includes at least one of dipropylene glycol butyl ether, alcohol ester dodeca, dipropylene glycol methyl ether, and propylene glycol butyl ether; the dispersant includes one of a block copolymer polyurethane or a long-chain linear acrylate; the thickener is a non-ionic hydrophobically modified polyurethane block copolymer; the defoamer includes a non-ionic defoamer, a molecular-level defoamer, a mineral oil defoamer, or a silicone defoamer.
9. The method for manufacturing a high-strength polypropylene-based battery shell material according to claim 7, characterized in that: In step S6.1, the antioxidant is a mixture of antioxidant 1010 and DLTP in a weight ratio of 3-4:7.